Milkfish Production and Ecology of Brackishwater Ponds Treated with Organic Versus Inorganic Fertilizers in Cochin, India - Joseph, Aneykutty; K., Jayasree Vadhyar (Fishery Technology, 2025)
The paper deals with a comparative study of growth, survival and yield of milkfish as well as the ecological characteristics of two brackish water culture ponds (0.042 ha each), one treated with organic fertilizer (cowdung) and the other with inorganic fertilizers (superphosphate and urea). Milkfish, Chanos chanos of 6 g average weight were stocked at a rate of 4500 fingerlings ha’1 in both the ponds. Remarkably better growth of fish (238 g), 86% of survival and gross and net productions of 852 and 825 kg ha"1 espectively, were obtained after 120 days of culture from the pond treated with cowdung, than from the pond treated with inorganic fetilizers which showed a growth of only 63 g, survival of 82% and goss and net productions of 226 and 199 kg ha0, respectively during the same period. The operational economics ofmilk fish production from the ponds has been compared. The rate of return on operational costs works out to be 298% in the pond treated with cowdung and 3% in the pond treated with chemical fertilizers.